Comparison Between Genetic Algorithm and Electromagnetism-Like Algorithm for Solving Inverse Kinematics - Yap, David F. W. (IDOSI Publications, 2012)
A comparison study between Electromagnetism-Like Algorithm (EM) and Genetic Algorithm (GA)has been presented in this work to solve the Inverse Kinematics (IK) of a four-link planar robot manipulator. The comparison is focused on some points for both algorithms like the accuracy of the results and the speed of convergence. Different target points have been taken to check the performance of each algorithm to solve the IK problem. The results showed that EM algorithm needs less population size and number of generations to get the true solution. There are multiple robot configurations at the goal points and both algorithms are able to find these solutions at each point. Self developed software simulator is used to display some of these solutions at each goal position.